Perception of organizational politics (POP) and its corollary toward employees job performances, citizenship behaviors and career developments - Kavitha, Ragupadzi (Universiti Malaysia Sarawak (UNIMAS), 2010)
This study explores the relationship between perception of organizational politics (POP) and it affects on the employees job performances, citizenship behaviors as well as their career development aspect. A survey method was used to collect data from samples from both private and government sector employees. Respondents was asked to respond to a number of questions in relation with their POP. The collected data was analyzed to test the study hypothesis by using statistical techniques such as Independent Sample T-test, One-Way ANOV A and Pearson Correlation analysis. The analysis result shows that nine of the alternate hypotheses are accepted except for one hypothesis which was rejected. Overall, the findings indicate that the POP is proven to affect the employee's job performance in the organization. Negative perception toward the organizational political activity will influence their job satisfaction as well as level of loyalty in the organization. Employees who believe that their organization has stepped into organizational politics have lower job satisfaction, organizational commitment, organizational citizenship as well as high work related stressors. Therefore, it is important for organization to acknowledge the political activities in the work setting and maintain the political activities to be at a minimum level in the organization in order to ensure an excellent and productive performance by their employees at all time.